2016
DOI: 10.1073/pnas.1605828113
|View full text |Cite
|
Sign up to set email alerts
|

DNA damage tolerance pathway involving DNA polymerase ι and the tumor suppressor p53 regulates DNA replication fork progression

Abstract: DNA damage tolerance facilitates the progression of replication forks that have encountered obstacles on the template strands. It involves either translesion DNA synthesis initiated by proliferating cell nuclear antigen monoubiquitination or less well-characterized fork reversal and template switch mechanisms. Herein, we characterize a novel tolerance pathway requiring the tumor suppressor p53, the translesion polymerase ι (POLι), the ubiquitin ligase Rad5-related helicase-like transcription factor (HLTF), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
161
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(184 citation statements)
references
References 76 publications
14
161
1
Order By: Relevance
“…This novel observation can imply that on a cell-by-cell basis, gH2AX response to replication stress is actually dampened by the knockdown of p53, and/or that p53 facilitates fork progression under stress. A stimulatory role of p53 in stressed fork progression was found by some studies (41,42) but not others (43). Resistance to AZD1775-induced replication stress at a replication fork level likely involves a RAD18-TLS polymerase kappa-dependent tolerance pathway and a RAD51-dependent fork protection pathway (13).…”
Section: Discussionmentioning
confidence: 96%
“…This novel observation can imply that on a cell-by-cell basis, gH2AX response to replication stress is actually dampened by the knockdown of p53, and/or that p53 facilitates fork progression under stress. A stimulatory role of p53 in stressed fork progression was found by some studies (41,42) but not others (43). Resistance to AZD1775-induced replication stress at a replication fork level likely involves a RAD18-TLS polymerase kappa-dependent tolerance pathway and a RAD51-dependent fork protection pathway (13).…”
Section: Discussionmentioning
confidence: 96%
“…(10,32) Some DNA damage repair is Erk1/2-dependent or accelerated by Erk1/2 activation. (33,34) It has also been reported that Pol ι can interact with p53, (35) which can activate Erk1/ 2. (36) Therefore, we hypothesize that Erk1/2 is activated by Pol ι via the DNA damage repair system.…”
Section: Discussionmentioning
confidence: 97%
“…It was shown that triplex-forming oligonucleotides are able to activate DNA recombination and DNA repair in addition to inducing genomic instability [77]. Intact p53 C-terminus is necessary for recognition of damaged DNA and recombination intermediates [2, 3, 7, 8, 63, 78, 79]. Triplex DNA may also elicit genetic instability by a roadblock to DNA replication and transcription elongation [80].…”
Section: Discussionmentioning
confidence: 99%
“…Triplex DNA may also elicit genetic instability by a roadblock to DNA replication and transcription elongation [80]. The DNA damage tolerance pathway and p53 regulates DNA replication fork progression according to a recent study [78]. It was shown, that the helical distortions and structural alternations induced by triplex formation may be recognized as “DNA damage” [80, 81].…”
Section: Discussionmentioning
confidence: 99%